Eliminating interlocks in deeply pipelined processors by delay enforced multistreaming - McCrackin, D.C. (IEEE transactions on computers, 1991)
The delay enforced multistreaming (DEMUS) processor architecture provides a simple, inexpensive ways of achieving high hardware utilization in deeply pipelined processors. Multiple streams share the pipeline in an interleaved fashion. Both the data dependency problem and the jump problem are prevented by enforcing enough interdispatch delay on each individual stream to prevent successive instructions from interfering with each other's execution. The structure and operation of a small DEMUS processor are presented, and four stream dispatching algorithms are compared by means of a simple simulation. Of the three implementable algorithms, the modified fixed delay (DEMUS/MFD) and encoded delay with fixed minimum (DEMUS/EDF) mechanisms yield the highest performance.< >